Dynamics of Modern Property in Brazil: social function, land regularization, and challenges for effectiveness - Batista, Leonardo Matheus Barnabé; Souza, Lucas Barbosa e; Cavalcante, Jéssica Painkow Rosa (Revista JRG de Estudos Acadêmicos, 2024)
This article addresses the evolution of modern property in Brazil in three distinct parts. Initially, it examines the emergence of modern property in the context of Western codifying phenomena, highlighting its liberal foundation and the debate surrounding the individualistic concept of ownership. The second part focuses on the idea of the social function of property in the Brazilian Federal Constitution, emphasizing the mitigation of the absolutist nature of property. The 1964 Land Statute is identified as a legal milestone that introduced requirements for the fulfillment of the social function of land property. The third section analyzes property rights as effectiveness, focusing on land regularization policy. It examines the construction of the rights of traditional communities and questions the adequacy of current legal categories for the effective guarantee of these rights, considering the new Latin American constitutionalism and socio-environmental perspective. The conclusion highlights the tension between individualism enshrined in property and social demands, pointing to the need for a profound revision of existing paradigms and a renewed commitment to social justice in the effective implementation of legally acquired rights.